A systematic theological comparison of religious iconography: Referring to Groeber and Kinkade - Rooyen, Johan A. van (HTS teologiese studies, 2023)
Iconography and symbolism of religion, correspondingly, are vital and convoluted aesthetic patterns and kinetics in a well-used foundational manner to transcend religious theories and the optical, audible and gesture depictions of religious intelligence with narratives. Iconography and symbolism of religion gain autonomy from all world religions. Subsequently, during the 20th centennial, a few academics emphasized the significance of religious spirit to persuade in citing religion as a rational entity. The symbolic condition of religion is alike viewed by a few academics of mythos and psyche as essential idiosyncratic with a religious explanation. Academics from provisional religionists, developmentalists and psychiatrists harvested with explanation the vast plethora of data on the emphasised views within religion, notably within association with East as well as Western religions. In the new liturgical theology of Christian formalities, additional appraisal of religiously emphasised syntax has transpired.Contribution: In this article, kinetics of symbols and visuals that are presented in a specific pattern and tenacious accord to the structure, subject matter and motives of the proposal are proclaimed to be among the most profound ways of experiencing and articulating religious details. Such patterns, as I think Prof. Johan Buitendag would agree, also add to the care and reinforced accords between sapiens3 with its domain that is revered or divine transcendental, metaphysical magnitude. That is what this article is about!